Analisa Strategi Meningkatkan Kualitas dan Produktivitas Layanan Di Laundry Dadok Tunggul Hitam Padang - Khairil Azmi; Muhammad Jamil; Faeza Rezi S (PT. Karya Inovatif Nusantara, 2024)
Increasingly fierce competition cannot be avoided by every company that wants to develop its business. The increasing intensity of competition and the number of competitors requires companies to always pay attention to customer needs and desires and try to meet customer expectations by providing more satisfying services than competitors do. Thus, only quality companies can compete and dominate the market. The aim of the research is to see what strategies analysis are carried out by the Dadok Tunggul Hitam Padang Laundry to improve the quality and productivity of its services. This research uses qualitative methods and is classified as field research with semi-structured interviews and documentation as data collection techniques. The findings from this research are that the Dadok Tunggul Hitam laundry has several strategies to improve its quality and productivity in serving its customers